2023
DOI: 10.1111/dar.13629
|View full text |Cite
|
Sign up to set email alerts
|

Trends in alcohol‐attributable hospitalisations and emergency department visits by age, sex, drinking group and health condition in Ontario, Canada

Abstract: Introduction: Alcohol-attributable harms are increasing in Canada. We described trends in alcohol-attributable hospitalisations and emergency department (ED) visits by age, sex, drinking group, attribution and health condition.Methods: Hospitalisation and ED visits for partially or wholly alcoholattributable health conditions by age and sex were obtained from populationbased health administrative data for individuals aged 15+ in Ontario, Canada. Population-level alcohol exposure was estimated using per capita … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A modelling study in England found the introduction of a 10% tax increase and minimum unit prices were more effective at reducing alcohol use and harm among men, as women were more likely to maintain their consumption and increase spending following the price policy ( Meier et al, 2021 ). Given our findings that women low volume alcohol users accounted for a greater proportion of all alcohol-attributable healthcare encounters than men low volume users and the growing evidence base that rates of alcohol-attributable harm have been increasing among women in recent years ( Erol and Karpyak, 2015 , Smith et al, 2023 ), understanding potential heterogeneous responses to universal alcohol policies is an important area for future research and can ensure prevention efforts reach all relevant equity-seeking subpopulations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A modelling study in England found the introduction of a 10% tax increase and minimum unit prices were more effective at reducing alcohol use and harm among men, as women were more likely to maintain their consumption and increase spending following the price policy ( Meier et al, 2021 ). Given our findings that women low volume alcohol users accounted for a greater proportion of all alcohol-attributable healthcare encounters than men low volume users and the growing evidence base that rates of alcohol-attributable harm have been increasing among women in recent years ( Erol and Karpyak, 2015 , Smith et al, 2023 ), understanding potential heterogeneous responses to universal alcohol policies is an important area for future research and can ensure prevention efforts reach all relevant equity-seeking subpopulations.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, both wholly and partially alcohol-attributable harm were directly estimated from administrative health records capturing all ED visits and hospitalizations in Ontario. Limitations of InterMAHP have been described in detail elsewhere ( Sherk et al, 2020 , Smith et al, 2023 ), including the use of relative risks from different countries and time periods which can reflect alcohol-attributable mortality when morbidity risks were not available. It was not possible to disaggregate former users into those with no lifetime alcohol use and those who stopped using in the past year for health-related reasons; this should be a consideration for future research with different data sources and methodologies as it may impact the estimation of alcohol-attributable healthcare encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Further, despite alcohol frequency and volume increasing among women, women still do not drink the same amount of alcohol as men. Men are much more likely to experience acute alcohol-attributable harms such as poisonings and injuries, given the volume of alcohol they may consume [13,29]. Further, externalising behaviours, more common among men, are associated with social inequities [30,31] and thus may result in engagement with aggressive or outwardly risky behaviours as a response to their social environments and level of drinking [32].…”
Section: Discussionmentioning
confidence: 99%
“…Existing work on the alcohol harms paradox suggests assessing the association between socio-economic position and alcohol-attributable harms by gender could be helpful for future research. This is important, while women experience fewer harms and were previously known to drink much less than men, the frequency of alcohol use in women has increased markedly over the last few decades and alcohol harms have increased significantly faster than men [12,13]. This distinction between chronic and acute alcohol-attributable harms is important, given the different alcohol use patterns associated with each type of harm.…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, results suggest that a HWL may have stronger effects on younger versus older when nutrition label elements co‐occur on packaging, when no label elements are present, or when the HWL only is present. This is a key finding as cohorts currently at mid‐life are increasing alcohol use and binge drinking, and experiencing alcohol‐attributable harm at greater levels than other population subgroups [62, 63].…”
Section: Discussionmentioning
confidence: 99%